2022
DOI: 10.3389/fnmol.2022.967472
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of neuronal injury transcriptional response identifies CTCF and YY1 as co-operating factors regulating axon regeneration

Abstract: Injured sensory neurons activate a transcriptional program necessary for robust axon regeneration and eventual target reinnervation. Understanding the transcriptional regulators that govern this axon regenerative response may guide therapeutic strategies to promote axon regeneration in the injured nervous system. Here, we used cultured dorsal root ganglia neurons to identify pro-regenerative transcription factors. Using RNA sequencing, we first characterized this neuronal culture and determined that embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…EnsembleTFpredictor identified five TFs predicted by both algorithms, and two of them, N-myc and Pax6, were shown to form physical complexes with SnoN to regulate granule neuron precursor development. In a second study, MORA, HOMER, and oPossum-3 were used to identify TFs that regulate genes differentially expressed during dorsal root ganglion (DRG) neuron axon regeneration [ 24 ]. EnsembleTFpredictor identified 43 TFs predicted by at least two methods, including known axon-regeneration TFs, as well as TFs not yet characterized in axon regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EnsembleTFpredictor identified five TFs predicted by both algorithms, and two of them, N-myc and Pax6, were shown to form physical complexes with SnoN to regulate granule neuron precursor development. In a second study, MORA, HOMER, and oPossum-3 were used to identify TFs that regulate genes differentially expressed during dorsal root ganglion (DRG) neuron axon regeneration [ 24 ]. EnsembleTFpredictor identified 43 TFs predicted by at least two methods, including known axon-regeneration TFs, as well as TFs not yet characterized in axon regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first tool performing this type of integration. Literature search and our experimental validation [ 23 , 24 ] demonstrated that MORA and EnsembleTFpredictor are highly effective in identifying functional TFs responding to a perturbation and unraveling novel TFs that cooperate with each other to exert synchronized responses. Consequently, MORA and EnsembleTFpredictor serve as easy and cost-effective hypothesis-generating tools to broadly assess TF activity, yielding new biological insights.…”
Section: Introductionmentioning
confidence: 99%
“…( 9 , 45 ). Others have shown that co-expression of CTCF with other TFs contributes to promoting axon growth ( 46 ). While we also found that injury-responsive genes were enriched for binding sites for CCCTC-binding factor (CTCF), these were significantly less numerous than the ones identified for cohesin.…”
Section: Discussionmentioning
confidence: 99%